An integrated platform for a high-throughput pharmacokinetic study of glycosides using a boronic acid-functionalized 96-well glass plate. Issue 64 (23rd July 2019) - Zhao, Ningning; Gu, Qianqian; Liu, Zhiqiang; Song, Fengrui; Pi, Zifeng; Liu, Shu
Abstract : The novel Vial@FPBA strategy was established for a large-scale pharmacokinetic study of glycosides, during which glycosides were absorbed into a boronic acid-functionalized 96-well glass plate and directly desorbed for UHPLC-MS/MS analysis. Abstract : The novel Vial@FPBA strategy was established for a large-scale pharmacokinetic study of glycosides, during which glycosides were absorbed into a boronic acid-functionalized 96-well glass plate and directly desorbed for UHPLC-MS/MS analysis. Hence, specific and high-throughput glycoside enrichment was achieved simultaneously. The LODs were reduced up to 50 times compared to the case of the methanol method. Meanwhile, sample pre-processing time was greatly saved by skipping the protein sedimentation and supernatant concentration steps.